Penerapan model problem based learning (PBL) dengan pendekatan technological, pedagogical, and content knowledge (TPACK) untuk meningkatkan pemahaman konsep geguritan siswa kelas V sekolah dasar - Meylia Wulandari; Chumdari Chumdari (Jurnal Pendidikan Dasar, 2026)
This study aims to improve conceptual understanding of geguritan material for fifth grade students of SD Negeri 1 Kepyar by implementing the Problem Based Learning (PBL) model with the Technological, Pedagogical, and Content Knowledge (TPACK) approach. Students' conceptual understanding ability is important to achieve learning objectives and improve the quality of learning. This study was conducted using a collaborative classroom action research (CAR) method. The results showed that the application of the Problem Based Learning (PBL) model with the Technological, Pedagogical, and Content Knowledge (TPACK) approach to geguritan material significantly improved students' conceptual understanding, with an increase in the average value from cycle I = 53.4 to cycle II = 71.9. The percentage of classical completeness also increased from 20% to 86.7%. This study contributes to the development of more innovative learning models and approaches, with the hope that the use of technology can improve students' conceptual understanding.